BETWEEN THE PUBLIC AND THE PRIVATE: INEQUALITY IN EDUCATION POLICY IN BONDOWOSO - Heridianto, Heridianto; Nawawi, Ahmad; Hasanah, Rodiatul (FORPIM PTKIS ZONA TAPAL KUDA, 2025)
Education has a strategic role as the main pillar in national and regional development. This article aims to evaluate the direction and implementation of education policy in Bondowoso Regency within the framework of equitable national development. With a qualitative approach and descriptive-analytical methods, this study analyzes national and local policy documents as well as the scientific literature related to public policy and social justice in education. The results of the analysis show that the implementation of education policies in Bondowoso still faces various challenges, such as inequality between public and private schools, low regional institutional capacity, and central policies that tend to be unresponsive to the local context. Private schools, especially those based on community and religion, have not received proportionate funding despite having an important role in expanding access to education. Therefore, it is necessary to reformulate education policies based on local needs, strengthen the capacity of local governments and multi-sector collaboration to encourage inclusive, equitable and quality education as a pillar of sustainable regional development.